An approach of the diffraction loss prediction using artificial neural network in hilly mountainous terrain. Issue 11 (23rd August 2017) - Lee, Changwon; Park, Sungkwon
Abstract: An artificial neural network based diffraction model for hilly mountainous terrain is proposed. The proposed diffraction model is applied to predict the path in the case of non‐line‐of‐sight. The input parameters of the proposed model are presented and their performance in the path loss prediction is compared with the results from traditional empirical diffraction models using measurement data taken in mountain areas.